From Bab el-Nasr to Matariya: A Tale of Two Wandering Sphinxes - Connor, Simon (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
In Autumn 2018, the decision was taken to remove two quartzite sphinxes from a modern reconstruction of a postern next to Bab el-Nasr, Cairo. The two statues were thus moved to the open-air museum of Matariya, where they were most probably standing in the first place, on the site of the ancient Heliopolis. This article intends to provide documentation concerning the journey of these two pieces that await to be published. They represent key pieces in the understanding of the fate of the sculptural material once adorning the ancient city of Heliopolis.